Insight Into Provenance and Variability of Atmospheric Dust in Antarctic Ice Cores During the Late Pleistocene From Magnetic Measurements - Lanci, Luca; Delmonte, Barbara; Salvatore, Maria Cristina; Baroni, Carlo (Frontiers in Earth Science, 2020)
We measured saturation isothermal remanent magnetization (SIRM), coercivity of remanence (Hcr) and insoluble dust concentration (IDC) of 52 ice samples from Vostok and EPICA Dome-C ice cores (Antarctica) as a measure of magnetic properties of the aerosol dust entrapped in the ice. Samples range in age from marine isotopic stage (MIS) 7 to 19 in EPICA Dome-C ice core and from MIS 1 to 11 in Vostok ice core. Data from ice samples were compared with 86 samples from possible source areas (PSA) from East Antarctica, and 10 samples from South America and New Zealand. Previous results from MIS 1 to MIS 6 found that magnetic properties of aerosol dust could be divided in two distinct groups characterized by high-Hcr and low-SIRMdust for glacial samples, and low-Hcr and high-SIRMdust, for interglacial samples. The new data from older ice samples highlighted several discrepancies from this expectation with significant differences between Vostok and Dome-C sites. Magnetic properties of Antarctic PSA sample show a large variability, however PSA samples from Victoria Land and few other, have magnetic properties compatible with that of the glacial dust, or more precisely with samples characterized by high dust flux. The new data from Pleistocene ice and from PSA samples confirm the South American and Antarctic provenance of the largest atmospheric dust load typical of glacial stages. On the other hand, we did not found any PSA sample with properties compatible with the highly magnetic samples (mostly from interglacial stages), which are characterized by low IDC. These samples from the oldest and deepest part of the cores revealed a more complex picture than previously outlined from the analysis of MIS 1–6, and show unusual magnetic properties which can be tentatively attributed to chemical.